Vinblastine Based Iron Oxide Nano Drug Delivery System - Mohammed S. K. Albermani (Journal of Global Pharma Technology, 2017)
Magnetic nanoparticles are a class of nanoparticles with significant properties which make them a highly promising to contribute in a drug design. The size depend property is the key issue that nondrug delivery system relaying on as well as the size of these submicron nanoparticles compared with the volume ratio. Many researchers in the being time focusing on the use of the innovated property of Magnetic nanoparticles applications in drug delivery systems due to their stability and biosafety compared with the others nanoparticles. Hence Iron Oxide have been chosen for this study and formulated by co-precipitation method with the size ranging between 50-100 nm in diameter the size and the morphology of the iron oxide were conformed using SEM. Vinblastine sulfate which is well known as a powerful chemotherapy against cancer have been incorporated with the iron oxide NPs and tested on MCF-7 a breast cancer cell line at different intervals of time 24hrs, 48hrs and 72hrs, a bright field and fluorescent image was taken to show the health growing of the cells. MTT survival assay have been conducted to measure the cytotoxity of the iron oxide-vinblastine and compare it with the pure vinblastine. The entire Vin- Fe3O4have shown more efficiency to inhibit the growth of MCF-7 cell line compared with the pure vinblastine. This formulation can be considered as a useful functional drug to cure cancer.